PanCircBase: An online resource for the exploration of circular RNAs in pancreatic islets - Sinha, Tanvi; Mishra, Smruti Sambhav; Singh, Suman; Panda, Amaresh Chandra (Frontiers in Cell and Developmental Biology, 2022)
Circular RNAs (circRNAs) are a novel class of covalently closed RNA molecules that recently emerged as a critical regulator of gene expression in development and diseases. Recent research has highlighted the importance of novel circRNAs in the biosynthesis and secretion of insulin from β-cells of pancreatic islets. However, all circRNAs expressed in pancreatic islets or β-cells are not readily available in the database. In this study, we analyzed publicly available RNA-sequencing datasets of the pancreatic islets to catalog all circRNAs expressed in pancreatic islets to construct the PanCircBase (https://www.pancircbase.net/) database that provides the following resources: (i) pancreatic islet circRNA annotation details (genomic position, host gene, exon information, splice length, sequence, other database IDs, cross-species conservation), (ii) divergent primers for PCR analysis of circRNAs, (iii) siRNAs for silencing of target circRNAs, (iv) miRNAs associated with circRNAs, (v) possible protein-coding circRNAs and their polypeptides. In summary, this is a comprehensive online resource for exploring circRNA expression and its possible function in pancreatic β-cells.